To what extent do the storage conditions of polyether‐based polyurethane have an impact on diazepam delivery?. Issue 43 (17th April 2020) - Maiguy‐Foinard, Aurélie; Masse, Morgane; Degoutin, Stéphanie; Genay, Stéphanie; Chai, Feng; Barthélémy, Christine; Odou, Pascal; Blanchemain, Nicolas; Décaudin, Bertrand
Abstract: Interactions between medical device material and the drug itself have been evoked for polyurethane and may lead to underdosing. Polyurethane, sterilization mode, and the crosslinking level of the polymer have an influence on sorption. The aim here is to evaluate the impact of polyurethane conservation time and conditions as well as sterilization mode. Two polyurethane extension tubes were tested, one sterilized by ethylene oxide and the second by gamma radiation. Forced degradation experiments were performed. After 3 and 6 months of incubation, thermal properties, diazepam delivery and cytotoxicity of leachates were assessed. Diazepam delivery differs significantly according to the version of polyurethane. Sterilization however has no impact on diazepam delivery. No cytotoxicity was observed whatever the infusion tube and the aging conditions. In conclusion, sterilization procedures do not induce polyurethane degradation, but high temperature/relative humidity/time storage conditions lead to a slight degradation in polyurethane. Abstract :